URBAN-RURAL DISPARITIES IN FOOD SECURITY: AN ANALYSIS OF HOUSEHOLD SURVEY DATA IN PLATEAU STATE, NIGERIA - Alade, Segun Peter; Su’an, Luka Ishaku; Abu, Christiana (FUDMA JOURNAL OF SCIENCES, 2023)
Food insecurity remains a critical concern in Nigeria, with significant disparities between rural and urban areas. This study aimed to assess differences in food security status between rural and urban households in Plateau State, Nigeria using discriminant analysis. Questionnaire data were collected from 140 households in one rural and one urban community. Eight measures of food security were assessed, including household size, income, food affordability and accessibility. Discriminant analysis results showed major differences between urban and rural households. Household size, food affordability and a tendency for food shortages were the most significant differentiating variables, with urban households having higher food security. The discriminant model correctly classified 89% of cases, demonstrating good predictive accuracy. Findings indicate substantial urban-rural disparities in food security, likely driven by factors like household size, income and food accessibility. Targeted policies and interventions in rural areas and for larger households may help address gaps in the affordability, availability and accessibility of food. Further research across wider geographic areas can validate and extend these results.
Keywords: Community; Discriminant; Food security; rural; urban